HIGH-IMPACT DESIGN FOR ONLINE COURSES BLUEPRINTING QUALITY DIGITAL LEARNING IN EIGHT PRACTICAL STEPS - Simunich, Bethany; Gregg, Andrea; Ralston-Berg, Penny (Routledge, 2024)
In a post-pandemic age when design expertise is in high demand, Simunich, Gregg, and Ralston-Berg offer the experience of working with an instructional designer to any faculty member. Written in an accessible "workshop" tone, this book systematically guides instructors through 8 practical steps with hands- on design documents and faculty-ID collaboration scenarios. With the help of HIDOC, new and seasoned instructors can successfully take their online courses from inception to launch, using resources typically made available only through consultation with an ID. This text is a must-have for institutions, schools, and departments interested in scaling quality online course design.